Using LyricsTraining Website in English Listening: Students’ Perception - Putri, Umayyah Tiara; Korompot, Chairil Anwar; Munir, Munir (Journal of Excellence in English Language Education, 2024)
LyricsTraining, a technology-enhanced learning platform, has proven itself as a valuable tool for improving students' English listening skills by providing a friendly and accessible learning environment for its users. The Technology Acceptance Model (TAM) framework provides a solid foundation for understanding how students engage with the platform. This study aims to leverage TAM to explore students' perceptions of using the platform for English listening. The TAM framework identifies factors influencing perceptions, such as navigation ease and content relevance, and enables educators to adapt teaching methods and enhance language learning outcomes, bridging traditional approaches with technological interventions. This research can contribute to technology-mediated language learning literature, offering insights for future research and improving language learning experiences through informed technological interventions, allowing instructors to develop more successful learning tactics. It can shed light on the psychological aspects that affect students' acceptance and performance with technology in learning environments, as well as how technology can be used to improve English language acquisition.